STUDI PERENCANAAN INSTALASI DAN DISTRIBUSI TENAGA LISTRIK HOTEL THE WESTIN JAKARTA - Waloyo, Tejo Faridh; Isnaeni, Isnaeni; Sutarno, Sutarno (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2011)
Hotel is a residence particularly for tourist and businessman to spend their time. Hotel The Westin Jakarta is one of hotels which located at M.H Thamrin street that has primary function as hotel andappartement/office. For the aim needs an installation and distribution design of electrical power well. Settingup for electrical circuitry which appropriate with Persyaratan Umum Instalasi Listrik (PUIL) 2000 in orderthat electrical installation effort carry out well to guarentee job safety and environment. The study of installation and distribution design of electrical power at Hotel The Westin Jakartaintends to describe about an installation and distribution electrical power that will be used in Hotel TheWestin Jakarta appropriate with PUIL 2000. Methods of investigation are (1) Documentation (2) Interview (3)librarywork. Based on analysis of data was obtained installation and distribution design that agree with PUIL2000 about 93,36% from three categories are analyzed they are cross-sectional area of cable, rated current ofelectrical devices, and choosing of protection conductor. Based on analysis data, it can be conclude that (1) installation and distribution design of electricalpower of The Westin Jakarta Hotel has appropriated PUIL 2000 because it has been completed gambarsituasi, gambar instalasi, one line diagram, gambar rinci, tabel bahan instalasi and uraian teknis. (2) Allpower cable has KHA upon the load current flows, for choosing the rating current of protection device hasappropriate, so, if the disruption happen in one of the panel it is not interfere with other panel. (3) There isdeviation PUIL 2000 in choosing of protection conductor about 18,9%.